2020
DOI: 10.1002/adts.202000174
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational Spectra of the OH Radical in Water: Ab Initio Molecular Dynamics Simulations and Quantum Chemical Calculations Using Hybrid Functionals

Abstract: The OH radical has remarkable features in aqueous environments. Studies of vibrational properties can uncover more information about this omnipresent radical. However, infrared spectra of the OH radical in water represent a challenging task. This work studies the OH ⋆ stretching vibration from the gas phase for OH ⋆-wn (w = water, n = 0-5) clusters to the bulk phase for OH ⋆-w31 via ab initio molecular dynamics (AIMD) simulations with B3LYP-D3 and the maximally localized Wannier function scheme. The infrared s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(88 citation statements)
references
References 136 publications
3
85
0
Order By: Relevance
“…To further investigate this issue, we performed ai MD simulations of OH(aq) using periodic DFT, in a unit cell [OH(H 2 O) 63 ] that is thought to be large enough to avoid finite-size artifacts. 29,32 One simulation employs the PBE0 + D3 functional at T = 370 K, consistent with the most recent hybrid DFT ai MD simulations of OH(aq), 35 except that the unit cell is twice as large in the present work. (Details can be found in Section S1 of the Supporting Information.)…”
supporting
confidence: 66%
See 1 more Smart Citation
“…To further investigate this issue, we performed ai MD simulations of OH(aq) using periodic DFT, in a unit cell [OH(H 2 O) 63 ] that is thought to be large enough to avoid finite-size artifacts. 29,32 One simulation employs the PBE0 + D3 functional at T = 370 K, consistent with the most recent hybrid DFT ai MD simulations of OH(aq), 35 except that the unit cell is twice as large in the present work. (Details can be found in Section S1 of the Supporting Information.)…”
supporting
confidence: 66%
“…The feature at smaller values of r O * O that is is typically associated with the hemibond is absent from the periodic simulation at T = 370 K, consistent with previous simulations at the same temperature but using a smaller unit cell. 35 At T = 310 K, however, one can just barely observe the appearance of a feature at r O * O = 2.2Å. Even at the higher temperature, the RDF is not zero at r O * O = 2.2Å although there is no distinct feature prior to the main hydrogen-bonding peak.…”
mentioning
confidence: 92%
“…This will definitely show how this thesis is a turning point for both system types as well as for other complicated systems. 36,41,42…”
Section: Introductionmentioning
confidence: 99%
“…[29][30][31][32] Perhaps for these reasons, the possibility of a hemibonded solvation motif seems not to have been considered in the analysis of recent x-ray experiments on OH(aq). 33 Recent ai MD simulations using hybrid functionals report no evidence of the feature traditionally associated with this motif, [34][35][36] namely, a peak at 2.2-2.3 Å in the radial distribution function (RDF) for oxygen. 26 In the present work, we use periodic DFT simulations at the PBE0 + D3 level 37,38 to demonstrate that the disappearance of this feature in hybrid DFT does not imply the absence of a hemibonded solvation motif.…”
mentioning
confidence: 99%
“…Hemibonding in • OH­(aq) was predicted in some of the earliest ab initio molecular dynamics ( ai MD) simulations using density functional theory (DFT), but these predictions were quickly rejected as artifacts of self-interaction error (SIE) associated with the use of semilocal functionals, since SIE is known to overstabilize 2c–3e bonds. , More recently, it has been suggested that the hemibonds observed in those early simulations might instead be artifacts of a too-small periodic simulation cell. Perhaps for these reasons, the possibility of a hemibonded solvation motif does not seem to have been considered in the recent analysis of ultrafast X-ray experiments on • OH­(aq) . The latest ai MD simulations using hybrid functionals report no evidence of the feature traditionally associated with this motif, namely, a peak at 2.2–2.3 Å in the radial distribution function (RDF) for oxygen . In the present work, we use periodic DFT simulations at the PBE0+D3 level , to demonstrate that the disappearance of this feature in hybrid DFT does not imply the absence of a hemibonded solvation motif.…”
mentioning
confidence: 99%